Mediating effect of job satisfaction on relationship between leadership style, job involvement, perceived organizational support and lecturers’ organizational commitment in Nigeria - Sakiru, Oladipo Kolapo (2019)
The level of organizational commitment among academic staff in Nigerian tertiary institutions has been generating serious concerns among education stakeholders. This is due to the important roles which academic staff plays in the overall quality and standard of the nation’s education. This study therefore investigated the mediating effect of job satisfaction on the relationship between leadership styles, job involvement, perceived organizational support and lecturer’s organizational commitment in Nigeria tertiary institutions. In this regard social exchange theory was used to examine the relationship and the mediating effect. In order to meet the objectives of the study a cross- sectional, correlational survey design was used and while Cochran (1977) formulae for sample size determination was used to calculate for the sample size. Standard self-administered questionnaire were used to gather data among 404 lecturers selected from the tertiary institutions in Lagos state, Nigeria. Descriptive analysis and Structural Equation Modelling (SEM) was conducted for data analysis. Prior to full utilization of the model, the researcher ensure the model meet the acceptance goodness-of-Fit indices: 2 (720) = 1268.064, p=0.00, 2 /DF=1.761, GFI=0.867; TLI=0.957, CFI=0.960; IFI=0.960, and RMSEA= 0.043. The findings of the study revealed that most of the respondent reported moderate in their response on the constructs: Organizational commitment, with (Mean=3.17, SD=0.86), leadership styles with (Mean=3.55, SD=0.84). Perceived organizational support is moderate (M=3.32, SD=0.81). These results mean that tertiary institutions lecturers have rated moderate in explaining their organizational commitment, leadership styles and perceived organizational support of their institutions. Also Overall score for job involvement and job satisfaction are moderate at (M=3.56 SD=0.90) and (M=3.42, SD=0.76). Respectively, the results of the Structural Equation Model analysis indicated that there is positive significant relationship between the leadership styles, job involvement, perceived organizational support and organizational commitment. Finally, the results revealed that job satisfaction mediate between leadership styles, perceived organizational support, job involvement and organizational commitment. In conclusion, it is recommended that practitioner, government and society should take great focus on job satisfaction, job involvement, perceived organizational support as well as leadership styles in order to improve academic staff organizational commitment. At the same time, reduce the turnover rate among lecturers of tertiary institutions in Lagos state, Nigeria. There is need to place more emphasis on lecturers development in the tertiary institutions. Therefore, this study suggested for more effective enhancement of predictors of organizational commitment in tertiary institutions in Lagos state, Nigeria. This study provide a unique contribution to research by developing a gap for future researchers by combining empirically grounded findings together with theoretical explanation from the literature. This study finding also highlighted some implications and recommendation for policy and practise toward improvement of lecturer’s commitment in tertiary institutions in Lagos State, Nigeria.